IMPACT OF MARRIAGE UNDER CHILDREN IN THE PERSPECTIVE OF MARRIAGE LAW AND THE CIVIL CODE - Rudolf Johanes Hasoloan; Azril Rozzaqi (Faculty of Law, Universitas Lampung, 2022)
Marriage is an inner and outer bond between two human beings in carrying out the household ark for social and state life. Nowadays, there are often early marriages which have a negative legal impact. The purpose of this study is to determine the impact of early marriage according to the Marriage Law and the Civil Code. This research was conducted using normative juridical research methods. This method includes library law research, which in this study will be carried out using literature (libraries), both in the form of laws and regulations, books, notes, journals and others. The results of this study indicate that there are many impacts caused by the occurrence of underage marriages. Judges usually grant marriage dispensation applications for underage couples because of the urgency to eliminate large losses. The state has set regulations on the age limit for marriage so that various problems arising from marriage can be resolved properly. Early marriage can cause social problems and various legal problems for children. Legal arrangements regarding marriage have been regulated by the state so that citizens must be subject to the law.